PENGUNAAN BAHAN CETAK Polyvinyl siloxane (PVS) DALAM PEMBUATAN GIGI TIRUAN PENUH - Syahrial . (Dentistry Faculty, 2018)
The quality of materials and dental impression techniques is a decisive factor in prosthodontictreatment. In the manufacturing of complete denture, the impression techniques and materials used forimpression are highly dependent on oral conditions and the dentist's konwledge about dentalimpression. There are two impression methods that are static impression and functional impression.These two stages of impressions can be combined in one technique using one kind of impressionmaterial and stock trayand producing functional border molding impression and basal seat. Thetechnique is known as combo technique. The impression tray used can be either an individual tray or astock tray. While the impression material using polyvinyl siloxane (PVS). The viscosity of theimpression material depends on the character and mobility or movement of the soft tissue covering thealveolar bone. Border molding, a low viscosity (heavier viscosity) material is required compared toprecise duplication of the denture base or using lighter viscosity material. The PVS material is goodfor impression on soft tissues of the oral cavity and for static and functional combined procedures. Ifdone according to the procedure, the results of combo techniqueimpression will be accurate andobtained every expected tissue detail.Keyword: complete denture, dental impression, polyvinyl siloxane, impression technique